2013
DOI: 10.1080/10255842.2012.662677
|View full text |Cite
|
Sign up to set email alerts
|

The influence of uncemented femoral stem length and design on its primary stability: a finite element analysis

Abstract: One of the crucial factors for short- and long-term clinical success of total hip arthroplasty cementless implants is primary stability. Indeed, motion at the bone-implant interface above 40 μm leads to partial bone ingrowth, while motion exceeding 150 μm completely inhibits bone ingrowth. The aim of this study was to investigate the effect of two cementless femoral stem designs with different lengths on the primary stability. A finite element model of a composite Sawbones(®) fourth generation, implanted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 39 publications
1
41
0
2
Order By: Relevance
“…the limit values of metrics such as in-out aspect ratio (0.02), edge length ratio (20), angular/volume skew (1/0.99), shape factor (0.01%), minimum dihedral angle (2), maximum dihedral angle (177), jacobian (0.019) or minimum edge length (0.01) were not violated. The mesh settings resulted in stem average micromotions comparable to those obtained by Reimeringer et al (2012). Node-to-node correspondence at the bone-implant interface was achieved and contact surface pairs and node sets for application of boundary conditions and loading were automatically created.…”
Section: Femur Implantation and Finite Element Contact Analysismentioning
confidence: 87%
See 2 more Smart Citations
“…the limit values of metrics such as in-out aspect ratio (0.02), edge length ratio (20), angular/volume skew (1/0.99), shape factor (0.01%), minimum dihedral angle (2), maximum dihedral angle (177), jacobian (0.019) or minimum edge length (0.01) were not violated. The mesh settings resulted in stem average micromotions comparable to those obtained by Reimeringer et al (2012). Node-to-node correspondence at the bone-implant interface was achieved and contact surface pairs and node sets for application of boundary conditions and loading were automatically created.…”
Section: Femur Implantation and Finite Element Contact Analysismentioning
confidence: 87%
“…Excessive bone-implant relative micromovements can compromise this stability (Pillar et al, 1986;Engh et al 1992;Soballe et al, 1993). These micromovements depend on implant design and positioning (Howard et al, 2004;Paratte et al, 2007;Andreaus et al, 2008;Park et al, 2009;Dopico-González et al, 2010;Reggiani et al, 2008;Bah et al, 2011;Reimeringer et al, 2012), possible interfacial gaps and the magnitude of forces acting on the proximal femur and patient anatomy (Pancanti et al, 2003). Therefore, when introducing new stem designs, it is essential that rigorous preclinical testing is conducted, both computationally and physically, since clinical problems associated with new designs may not be evident for some time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These SSs focus on metaphyseal fixation. Reimeringer et al, [6] in an analysis of a finite element model, demonstrated that reducing stem length to <105 mm was not associated with the stability of implants. SS designs depend upon a stable metaphyseal fit and require optimal proximal load transfer, and are beneficial to conserve bone mass and reduce thigh pain.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloy (Ti-6Al-4V) and aluminium (Aluminium_2014) properties in the NX material library were assigned to the fixation and the constraining rig, respectively. The use of homogeneous material properties for the fourth-generation sawbone material is consistent with FE work reported by Elenes et al, 16 Reimeringer et al 17 To simulate the curing of epoxy at the cut, the material properties of the mesh strip which represents the fracture were varied such that its density and Young's modulus were at fractions of the original values. The Poisson's ratio remained unaltered.…”
Section: Methodsmentioning
confidence: 93%